The Gross-to-Scope Program for Gross Room Personnel: An Innovative Initiative for Providing Case Follow-Up and Education to "Close the Pathology Loop". (16th February 2021) - Imblum, Brittney; Stern, Evan; Fortuna, Danielle
Gross room personnel (GRP) work alongside pathologists in grossing, frozen section, and autopsy. We observed that gross room personnel desire follow-up and feedback on the specimens they gross or autopsies they perform. Our goal was to create a sustainable educational program for gross room personnel. Our primary focus was to impact team dynamic, morale, and fulfillment. We assessed the need for an educational program through a preprogram survey, which contained 11 subjective statements scored on a scale from 1 to 10 (1—strongly disagree and 10—strongly agree). These statements assessed topics of current follow-up and team dynamic (core statements), perceived effect of current follow-up, and prospective impact of case follow-up. Core statements received relatively low scores (ie, the perception of being "an integral part in making a diagnosis" received only a mean score of 6.7). In response, we established the Gross-to-Scope educational program hosted by pathology trainees and attendings. This program is comprised of monthly one-hour conferences to discuss/review cases and highlight special topics of interest (ie, "What is a radial margin anyway?"). We distributed the same surveys after the first and fourth conferences and found a statistically significant increase in the mean responses to core statements after the first conference ( P = .041). The trend is similar after four conferences. Overall our program addresses various needs by providing educational opportunities for gross room personnel, which strengthens morale and recognizes hard work, and by fostering a working relationship between gross room personnel and pathologists.